Narrative theory and therapy in the post-truth era - Yılmaz, Recep, 1982-; Koç, Bozkurt, 1970- (Advances in linguistics and communication studies (ALCS) book series., 2022)
"This book focuses on the structure of the narrative and the possibilities it offers for therapy as well as the Post-Modern sources of spiritual conflict and how to benefit from the possibilities of the narrative while healing conflict, offering research on new concepts and models to be created"--